The Future of Cabinet Government in New Zealand: The Implications of MMP for the Formation, Organization and Operations of the Cabinet - Boston, Jonathon (School of Management Working Papers, 1994)
This paper considers the implications of the impending introduction of the mixed-member proportional (MMP) electoral system in New Zealand for the formation, organization and operations of the Cabinet. The literature on coalition government is surveyed and the likely forms of government under MMP are outlined. The paper then explores the dynamics of multi-party government, including the selection of the Prime Minister, the allocation of portfolios, and the internal organization of the Cabinet. Consideration is also given to the possible impact of MMP on the doctrines of individual ministerial responsibility and collective responsibility, and the case for appointing non-MPs as Cabinet ministers is examined. It is argued that the implications of MMP for the operations of the Cabinet will depend primarily on whether the governments which are formed are single-party minority governments, multi-party minority governments, or multi-party majority governments. The type of government which is most likely will in turn depend on the nature and evolution of the party system and any changes in the constitutional conventions relating to the formation of governments and the dissolution of Parliament.